Managing sales leads : - Obermayer, James (Thomson/South-Western, 2007)
Sales leads are what successful marketing is all about. That's where the money is. Good, qualified leads make sales forces more efficient, more effective, and — bottom line — more profitable. Add in today’s tough economy and the skills needed to generate and manage leads are even more vital. Offering a research-based, comprehensive treatment of this critically important marketing function, The Executive’s Guide to Managing Sales Leads delivers an excellent hands-on reference to every manager — from midlevel sales and marketing managers to senior-level corporate execs — at companies of every size, especially the midsize to Fortune 100 category.